Determinants of Compliance with Pulmonary Tuberculosis Medication - Rohmawati, Puji; Sekarwati, Novita; Damayanti, Susi (Disease Prevention and Public Health Journal, 2024)
Background: Tuberculosis is an infectious disease caused by the Mycobacterium tuberculosis bacillus. Basic Health Research data in 2018 showed that the prevalence rate of TB in Indonesia was 4%. Data from Gamping II Health Center with a total of 37 drug-sensitive and drug-resistant cases and a 90% drug compliance rate, there was only 1 DR-TB patient who was not compliant with taking medication. This aims to know the Determinants of Adherence to Taking Pulmonary TB Medication. Methods: This study was conducted in the working area of Gamping II Health Center. This study is an observational analytic study with a cross-sectional approach. Samples were taken by a total sampling method of as many as 37 people. The measuring instrument used a questionnaire. Data were processed and analyzed using the Chi-square test with a significance level of ρ<0.05. Results: This study shows that of the 37 respondents with pulmonary tuberculosis, 22 (59.5%) respondents were compliant with taking medication and 15 (40.5%) respondents were not compliant with taking medication. Analysis using the chi-square test showed that there was a relationship between knowledge (ρ=0.009), family support (ρ=0.022), and health worker support (ρ=0.025), towards compliance with taking medication. While not related to patient motivation and access to health services. Conclusion: Of the three most dominant variables affecting adherence to taking medication is the support of health workers. From knowledge, family support and health worker support have a probability of 32.4% for adherence to taking medication in patients with pulmonary tuberculosis.